Antimicrobial and antibiofilm activities of marine sponge-associated bacteria against multidrug-resistant Staphylococcus spp. isolated from canine skin. (March 2021) - Nunes, Suzanne de Oliveira; Oliveira, Bruno Francesco Rodrigues; Giambiagi-deMarval, Marcia; Laport, Marinella Silva
Abstract: Dogs play important roles in our society, thus the concern for their health becomes imperative. Staphylococcus spp. are commensal bacterium frequently isolated from canine skin and recognized as zoonotic agents. These bacteria have been becoming increasingly resistant to antimicrobials used to treat infections and to produce biofilm, which further increases their virulence capability and resistance. In this context, sponges-associated bacteria are known as prolific sources of substances with antimicrobial activities, representing a potential to integrate the arsenal of drugs for clinical use. In this study, 121 strains of Staphylococcus isolated from healthy or infected dogs were characterized according to their resistance to antimicrobials, as well as to their biofilm production ability. From the total of strains, 82 were resistant to at least one antimicrobial and 40 were multidrug-resistant (MDR). Furthermore, 117 out of 121 were capable to produce biofilm, and within those 36 were classified as strong biofilm producers. A set of fifteen bacterial strains previously isolated from marine sponges were also evaluated for antimicrobial and antibiofilm activities. Among the marine bacteria with antimicrobial activity, eight inhibited the growth of more than 50% of the MDR Staphylococcus . In addition, the cell-free supernatant obtained from five sponge-associated bacteria cultures was able to disaggregate more than 50% of the mature biofilm staphylococcal cells. The organic extracts (256 μg/mL) from two potential strains, Pseudomonas fluorescens H40 and H41, dissociated the biofilm of a strain classified as MDR and strong biofilm producer in 88.5% and 91.3%, respectively. These marine Pseudomonas strains also exhibited a strong activity of antimicrobial and antibiofilm substances. The results suggest that the sponge-associated bacteria analyzed could be potential sources of antimicrobial and antibiofilm substances against MDR and biofilm producers Staphylococcus isolated from canine skin. Highlights: Resistance to antimicrobial is widespread among Staphylococcus isolated from canine skin. There is a high prevalence of biofilm-producing Staphylococcus spp. isolates from healthy and sick dogs. Sponge-associated bacteria are source of antimicrobials against multidrug-resistant Staphylococcus isolated from dogs. dogs. Substances from sponge-associated Pseudomonas could represent a strategy to dissociate the biofilm of the Staphylococcus.